ANALYSIS OF WASTE MANAGEMENT AT THE PON EVENT AT THE MULTIPURPOSE ASTAKA MEDAN PANCING SPORT CENTER - Munthe, Ni’matul Ulya; Nanda, Meutia; Aisyah, Siti Nur; Hasibuan, Rafiqoh; Wulandari, Tri; Pohan, Rahmaidah; Nasution, Nurul Indah (HEARTY, 2025)
The 2024 National Sports Week (PON) has the potential to increase the amount of waste generated at the Astaka Medan Pancing Multipurpose Sport Center because this event will increase the number of visitors in the area around the competition location. This study aims to analyze waste management at the Astaka Medan Pancing Multipurpose Sport Center during the 2024 National Sports Week (PON). The research method used is descriptive qualitative, with data collection through observation, in-depth interviews, and documentation. The results of the study indicate that although there was an increase in the frequency of waste collection during the event, the existing trash bin facilities were inadequate and with a waste sorting pattern between wet and dry waste. A lot of trash was scattered in public areas, indicating ineffective waste management. This study advocates for the organizers or the government in this case the Environment and Forestry Service to add waste management facilities (trash cans, plastic sacks) in areas where there are many gatherings of people and make posters appealing to dispose of trash in its place, as well as improving coordination with volunteers and related agencies. With these steps, it is hoped that waste management at the Astaka Medan Pancing Multipurpose Sport Center can be improved, creating a cleaner and healthier environment during major events such as PON XXI Aceh-Sumut 2024.